Colonial Narrative in Giacomo Puccini’s “Madama Butterfly” in the Productions in Bregenz, Venice and Frankfurt 2022/2023 - Yefimenko, Adelina (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
Relevance of the study. The relevance of the article. In musical theatre, literature, cinema, and painting, the image of Madame Butterfly has been and continues to be the subject of both artistic and socio-political debate. The significance of the figure of Butterfly goes far beyond the worldfamous opera character. Various productions of the opera since the fin de siecle period prove the casualness of Madame Butterfly's repertoire leadership on the world stage. The main objective of the study and the scientific novelty. The article raises the question of the reasons for the opera's popularity in our time and analyses 1) the colonial discourse of the libretto, which goes beyond the limits of a purely Japanese discourse, and 2) various productions of the opera in Bregenz, Frankfurt, and Venice, in which the colonial narrative is asserted from different angles. The trajectory of the colonial narrative from Pierre Loti's Madame Chrysanthemum to Giacomo Puccini's Madama Butterfly clearly outlines the transformation of Japaneseism from an arts and crafts artefact to the Liebestod tragedy and critique of Japanese-Euro-American international relations. The issue of Madame Butterfly in various traditional or innovative media formats reveals, in one way or another, the transformation of the topos of exoticisation of colonised space. Behind the beauty of Italian bel canto in the image of Cio-Cio-San, the directors recognise and embody on stage the apocalypse of human relations in the context of systemic human rights violations. The interpretive analysis of three different productions revealed a systematic shift in the opera's lyrical and aesthetic emphasis to ethical ones. The methodology of the article is: in each of the three analysed productions, the colonial conflict is expressed in a different way, which the characters comprehend from within their hearts, upbringing, mental orientations, social environment and national traditions. Results / findings and conclusions. We live in a globalised world in which Japanese art and culture are equal parts of world culture. That is why the analysed stage versions of Madame Butterfly either deliberately avoid clichéd Japaneseisms or use them rather on the level of ciphers, hints, and associations. As conceived by Michael Levine, the set designer of the Bregenz production, the ink drawings on the associated papyrus on the stage allude to the traditions of ancient Japanese art. The costumes imitate the Japanese figures of the Kabuki theatre. Such ciphers reveal the beauty of old Japan. The figures of the Americans are stylised in the fashion of the twentieth century. The issues raised by the director Alex Rigola and set designer Mariko Mori in the Viennese production of Madame Butterfly — criticism of the complexes and stereotypes of the conventional view of man, woman, and the role of the individual in the context of a conflictual clash of polar mentalities — correspond to Andreas Homoki's Madame Butterfly, but lack direct political connotations. The director directed the peculiarity of the Frankfurt production in the direction of the Japanese philosophy of existence. An empty stage, the dominance of white and black, the image of Butterfly in colour dynamics from red to silver — this is how the stage graphics in the tradition of Johannes Leiaker's Japanese minimalism were stripped of external clichés. The abstract space became an apology for the straightforwardness associated with the signs of traditional Japanese architecture. The colonial narrative of Madame Butterfly is promising for further research of various repertoire operas in terms of the socio-political position of contemporary directors.